Multiplicity dependence of pion, kaon, proton and lambda production in p-Pb collisions at √ˢɴɴ = 5.02 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Adare, A.M.; Aggarwal, M.M.; Aglieri Rinella, G.A.; Agnello, M.; Agócs, A.G.; Agostinelli, A.; Ahammed, Z.; Ahmad, N.; Ahmad Masoodi, A.; et al. (Elsevier, 2014)
In this Letter, comprehensive results on π±, K±, K⁰ₛ, p(p̄) and Λ(Λ̄) production at mid-rapidity (0 < yCMS < 0.5) in p–Pb collisions at √ˢɴɴ = 5.02 TeV, measured by the ALICE detector at the LHC, are reported. The transverse momentum distributions exhibit a hardening as a function of event multiplicity, which is stronger for heavier particles. This behavior is similar to what has been observed in pp and Pb–Pb collisions at the LHC. The measured Pᴛ distributions are compared to d–Au, Au–Au and Pb–Pb results at lower energy and with predictions based on QCD-inspired and hydrodynamic models.
Keywords: π± production; K± production; https://purl.org/pe-repo/ocde/ford#1.03.03